1986
DOI: 10.1177/089124168601500205
|View full text |Cite
|
Sign up to set email alerts
|

The Social World of Shuffleboard

Abstract: In this article the author examines a leisure social world among senior citizens.Specifically, the social world of shuffleboard incorporates participants from several regions of the country that share meanings, events, procedures, and forms of communication. Attention is focused on "shuffling" as an expressive leisure activity and the attendant contingencies that may enhance or detract from a commitment to and integration in the social world. Secondarily, aspects of the shuffleboard subculture are highlighted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The social world construct has been used by researchers to examine various activities as forms of serious leisure. For example, Snyder (1986) examined senior citizen participation in the social world of shuffleboard and found the social world to consist of beginners, regulars, and insiders, based on the level of involvement and career stages. Other researchers have used the social worlds perspective to explore music making (Finnegan, 1989), contract bridge (Scott & Godbey, 1992, 1994, barbershop singing (Stebbins, 1996), adult amateur ice skating (McQuarrie & Jackson, 1996), tournament bass fishing (Yoder, 1997), mushroom collecting (Fine, 1998), and dog breeding (Baldwin & Norris, 1999) as serious leisure activities.…”
Section: Introductionmentioning
confidence: 99%
“…The social world construct has been used by researchers to examine various activities as forms of serious leisure. For example, Snyder (1986) examined senior citizen participation in the social world of shuffleboard and found the social world to consist of beginners, regulars, and insiders, based on the level of involvement and career stages. Other researchers have used the social worlds perspective to explore music making (Finnegan, 1989), contract bridge (Scott & Godbey, 1992, 1994, barbershop singing (Stebbins, 1996), adult amateur ice skating (McQuarrie & Jackson, 1996), tournament bass fishing (Yoder, 1997), mushroom collecting (Fine, 1998), and dog breeding (Baldwin & Norris, 1999) as serious leisure activities.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, play is frequently a backdrop for studying more "serious" topics like festivals, sport, games, social networks, friendships, or aging (e.g., Fournier & Fine, 1990;Gibson, Ashton-Shaeffer, Green, & Corbin, 2002;Green, 1998;Kalab, 1992). Or, play emerges as important during a study initially focused on another concept (e.g., Fine, 1987Fine, , 1991Scott & Godbey, 1994;Snyder, 1986). Cheang's (2002) study of older adults' and fast food restaurants, for example, concluded that the main reason for daily visits was because the restaurant became a "play area" (p. 371).…”
Section: Literature Review Play and Liminalitymentioning
confidence: 99%